Gesundheit & Bewegung - Kesztyüs D; 2; Steinacker JM (Dynamic Media Sales Verlag, 2017)
Non-communicable, chronic diseases like type 2 diabetes, cardio-vascular diseases and cancer are meanwhile the most frequent causes of death and contribute to the rising costs in health care. The current focus on therapeutic procedures and medication requires more health promoting, preventive approaches to improve public health and thereby control costs. Decisions on measures that counteract rising costs in health care need to be evidence-based to ensure the responsible use of limited resources. This is accomplished by health-economic analyses of the cost-effectiveness of a measure, since both costs and effects are considered.Physical inactivity is one of the most crucial, modifiable risk factors of morbidity and mortality, therefore physical activity promoting interventions for schoolchildren should be first priority. In fact,althoughmeasures to promote physical activity in children are widespread, economic evaluations of these interventions are still very rare. This review articlepresents successful school-based interventions with proven cost-effectiveness. The assessment of cost-effectiveness is illustrated based on the examples of the German URMEL-ICE project and the Join the Healthy Boat health promotion programme. Both programmes were, with costs per child and year of 24.09 and 25.04 respectively, below the threshold of 123.24, determined by the parental willingness to pay.A practical and sensitive outcome measure for the determination of the effectiveness of a physical activity promoting intervention is the waist-to-height ratio (WHtR), a measure of abdominal obesity. Even without considerable weight loss, the exercise-induced reduction of abdominal fat mass generates health benefits.KEY WORDS: Cost-Effectiveness, Health Promotion, Exercise, Abdominal Obesity, Childhood